Quantifying continental collision dynamics for Alpine-style orogens - van Agtmaal, Luuk; van Dinther, Ylona; Willingshofer, Ernst; Matenco, Liviu (Frontiers in Earth Science, 2022)
When continents collide, the arrival of positively buoyant continental crust slows down subduction. This collision often leads to the detachment of earlier subducted oceanic lithosphere, which changes the subsequent dynamics of the orogenic system. Recent studies of continental collision infer that the remaining slab may drive convergence through slab roll-back even after detachment. Here we use two-dimensional visco-elasto-plastic thermo-mechanical models to explore the conditions for post-collisional slab steepening versus shallowing by quantifying the dynamics of continental collision for a wide range of parameters. We monitor the evolution of horizontal mantle drag beneath the overriding plate and vertical slab pull to show that these forces have similar magnitudes and interact continuously with each other. We do not observe slab rollback or steepening after slab detachment within our investigated parameter space. Instead, we observe a two-stage elastic and viscous slab rebound process lasting tens of millions of years, which is associated with slab unbending and eduction that together generate orogenic widening and trench shift towards the foreland. Our parametric studies show that the initial length of the oceanic plate and the stratified lithospheric rheology exert a key control on the orogenic evolution. When correlated with previous studies our results suggest that post-detachment slab rollback may only be possible when minor amounts of continental crust subduct. Among the wide variety of natural scenarios, our modelling applies best to the evolution of the Central European Alps. Furthermore, the mantle drag force may play a more important role in continental dynamics than previously thought. Finally, our study illustrates that dynamic analysis is a useful quantitative framework that also intuitively explains observed model kinematics.